Substitution of Muriate of Potash by Common Salt in Banana Musa (AAA group CAVENDISH subgroup) Robusta - Sunu S (Department of Soil Science and Agricultural Chemistry, College of Agriculture, 2001)
A field experiment was conducted III the College of Agriculture, Vellayani during August 1999 to June 2000 to study the extent of substitution of K of muriate of potash by Na of common salt in banana cv. Robusta. Four treatments involving four levels of K at 25, 50, 75 and 100 per cent of recommended dose and four treatments substituting K with N a at 25, 50, 75 and 100 per cent were tried in RBD with three replications. The plant growth parameters like plant height, pseudostem girth, number of functional leaves and LAI varied significantly due to treatments at all growth stages. These parameters in the 100 per cent K and 50 per cent K plus 50 per cent Na treatments were on par at all growth stages. Chlorophyll content and RLWC showed an increase with the addition of Na along with K. Highest bunch yield was recorded in the 50 per cent K plus 50 per cent N a treatment followed by the yield in the lOO per cent K treatment. The yield attributes like length of bunch, number of hands per bunch, number of fingers per bunch, length and girth of fingers reflected similar trends.